Arbejdersang i Danmark siden 1800-tallet - Nygaard, Bertel (Arbejderhistorie, 2026)
Since the early inklings of a distinct workers’ movement in 1840s Denmark, songs and the practices of communal singing have played key roles in forming the movement. The establishment of the Social Democratic labour movement in the 1870s was bolstered by the proliferation of march songs programmatically expressing the unity of the workers as a class with socialist demands. When the first edition of the danish Arbejdersangbogen (the Workers’ songbook) was published in 1926, such songs could already be felt as old-fashioned. While a few of the most solidly-rooted marches survived as key elements in the musical canon of the movement, particularly U.P. Overby’s Socialisternes march(march of the socialists) from 1872, new additionsto the social-democratic repertoire tended to be less manifestly political. Meanwhile, a distinct Communist song repertoire carried the mantle of programmatic marches into the interwar years, though mainly in the shape of translated german or Russian revolutionary marches. By the 1930s, however, the discursive turn of both Social Democrats and communists towards a rhetoric of the ‘people’ was reflected in the songs, too, pushing the repertoire of workers’ songs closer to that of the folk identities in the dominant, non-socialist Højskolesangbogen (the songbook of the folk high school). The new left of the 1960s integrated a more composite sense of progressive subjectivity into a wider range of musical expressions, borrowed from folk and rock music. Today, the spirit of protest lives on in significant sectors of popular music yet tends to be detached from the musical traditions of the socialist labour movement.